The Impact of Classroom Architecture and Pedagogical Strategies on University Students’ Disruptive Phone Usage in Calculus - Harris, Isabel; Lanius, Melinda (Teaching and Learning Inquiry, 2025)
Personal phone usage—from group messaging to social media scrolling to online window shopping—is widespread in university classrooms. Numerous studies have documented how the presence of cell phones in the undergraduate classroom is more harmful than beneficial. Nevertheless, many educators are reluctant to enact and enforce a phone-free classroom, believing that, as adults, undergraduate students have the right to self-regulate. In this study, we utilize classroom observation data to explore how features of the learning environment, such as classroom architecture and instructor pedagogical strategies, can impact students’ propensity to reach for their phones in the middle of a calculus lesson. Further, we use student survey responses to compare overall phone usage to confidence in their knowledge and conceptual understanding of a lesson’s primary learning objective. Our results suggest that the learning environment itself, in particular the pedagogical strategies employed and the classroom architecture, can foster self-regulation amongst students without the instructor having to actively enforce a strict no-cell phones policy.